Analysis of the Budgetary Process of the European Union - Andrei PETROIA (Eastern European Journal of Regional Studies, 2016)
The European Union is one of the most significant economic and politic power of the world. Understanding its model of functioning brings us closer to understanding the current situation and the trends of development of the world. The budgetary process is only one of the interesting aspects of the functioning of the European Union. Also, being given the context of the Budget notion, the European Union budget represents an interesting research topic. The result of the research revealed information regarding the European Union budgetary process. Following the flow of the research, it offers clues to understanding the effectiveness and the success key of this mechanism.